Hubungan derajat friedman tounge position dengan nilai apnea-hypopnea index dan nilai low oksigen saturation pada pasien obstructive sleep apnea - Ahmad Effendi; Willy Yusmawan; Anna Mailasari Kusuma Dewi; Zulfikar Naftali; Muyassaroh Muyassaroh; Dwi Antono; Herlina Suryawati; Kanti Yunika (RSUP Dr. Kariadi, 2022)
ABSTRACT Background: Obstructive Sleep Apnea (OSA) is characterized by an airway obstruction that causes breathing to stop momentarily, either totally or partially. OSA can cause serious complications. The definitive diagnosis of OSA with polysomnography (PSG). PSG is not widely available in health facilities, Friedman tongue position (FTP) examination is expected to be an initial simple examination that can be done to diagnose patients with suspected OSA. Objective: To determine the relationship between the degree of FTP with the Apnea Hyponea index (AHI) andvalues Low saturation (LSAT)in OSA patients at Dr. Kariadi Semarang. Methods: Cross-sectional study design, samples were taken from patients diagnosed with OSA by polysomnography in May – July 2021. AHI and LSAT values ??were taken from polysomnography results. FTP is determined by physical examination of the throat. Data analysis with Spearman correlation test. Results: The highest number of samples was 44 male, 32 samples (72.7%). The highest age group was 46-65 years, 26 (59.1%), the youngest was 18 years and the oldest was 81 years, the mean age was 64 years +17-81 years. , the most FTP results are type 2, the most AHI values ??are severe degrees, the most LSAT values ??are moderate degrees. There is a very strong positive significant relationship between the degree of FTP and the AHI value, there is no significant relationship between the degree of FTP and the LSAT value. Conclusion: There is a relationship between FTP and the AHI value, there is no FTP relationship with the LSAT value Keywords: Obstructive sleep apnea, friedman tongue position, Apnea-Hyponea index, Low saturation.